2010
DOI: 10.1111/j.1747-4477.2010.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of the technical quality of root canal fillings performed by dental students

Abstract: The objective of this study was to evaluate radiographically the technical quality of root canal fillings performed by dental students at the School of Dentistry, University of the West Indies. The school's database between 2000 and 2004 was investigated for patients with completed root canal treatment. The final sample consisted of 198 patients with 288 root-filled teeth and 460 canals. The length, presence of voids, taper, curvature of canal and fractured instruments were recorded and scored. Chi-squared ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 18 publications
(38 reference statements)
7
27
5
Order By: Relevance
“…Poor technical quality of root fillings has also been reported in many studies that evaluated the performance of students when using hand files (8)(9)(10)(11). Rafeek et al (11) found that the percentage of "acceptable" root fillings was as low as 10.9%, which was close to the 13% reported previously (10).…”
Section: Introductionsupporting
confidence: 51%
“…Poor technical quality of root fillings has also been reported in many studies that evaluated the performance of students when using hand files (8)(9)(10)(11). Rafeek et al (11) found that the percentage of "acceptable" root fillings was as low as 10.9%, which was close to the 13% reported previously (10).…”
Section: Introductionsupporting
confidence: 51%
“…If the line intersected the root apex, the canal was considered straight. Otherwise, it was considered curved [3, 10]. …”
Section: Methodsmentioning
confidence: 99%
“…Although it is a highly predictable and successful procedure [2], several studies have reported a low percentage of technically adequate root fillings (10.9–55%) [1, 311]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the adequacy of RCT performed by undergraduate students as varying between 33% and 70% [13,19]. Assessment of treatment quality and frequency of procedural errors will help improve educational programs and enhance health services [14,20].…”
Section: Introductionmentioning
confidence: 99%